Enduring Ambiguity: What Is European Literature? Matthias Nawrat in Conversation with Monika Woltig - Wolting, Monika; NAWRAT , Matthias (Transfer. Reception Studies, 2019)
Matthias Nawrat is a Polish-German author living in Germany born in Opole, Poland. He moved with his family to Bamberg in 1989. He was awarded the Adelbert-von-ChamissoFörderpreis, was nominated for the Deutscher Buchpreis, received the Bremen Literature Prize and the Alfred Döblin Medaille. His most important novels were "Wir zwei allein" (2012), "Die vielen Tode unseres Opas Jurek" (2015), and "Der traurige Gast" (2019).